The Effect of Macroeconomic Variables and International Stock Indices on Sharia Market Index in Indonesia and Malaysia - Mita Agustiani; Umi Widyastuti; I Gusti Ketut Agung (International Forum of Researchers and Lecturers, 2025)
The objective of this study is to examine whether the macroeconomic variables Exchange Rate, Money Supply (M2), and the international stock indices Dow Jones Islamic Market (DJIM) and Dow Jones Industrial Average (DJIA) have an influence on the movement of Sharia stocks in Indonesia and Malaysia (Jakarta Islamic Index and FTSE Bursa Malaysia Hijrah Shariah Index). The analytical method used in this research is multiple regression analysis. The data utilized are monthly data spanning the period from January 2015 to December 2024. The results of the study indicate that the Jakarta Islamic Index (JII) is significantly influenced by the Exchange Rate and the Dow Jones Industrial Average (DJIA). Specifically, both the Exchange Rate and DJIA show effects that are consistent with the hypothesis expectations. The Exchange Rate has a negative and significant effect on the Jakarta Islamic Index (JII), while the DJIA has a positive and significant effect. Meanwhile, the Money Supply (M2) and the Dow Jones Islamic Market (DJIM) are not found to have a significant effect on the Jakarta Islamic Index (JII). The FTSE Bursa Malaysia Hijrah Shariah Index (FHSI), on the other hand, is significantly influenced by the Dow Jones Islamic Market (DJIM). Specifically, DJIM has a positive and significant effect on FHSI. Conversely, the Exchange Rate, Money Supply (M2), and Dow Jones Industrial Average (DJIA) are not found to have a significant effect on the FTSE Bursa Malaysia Hijrah Shariah Index (FHSI).